2017
DOI: 10.1007/s00109-017-1566-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory effect of galectin-1 in a murine model of atopic dermatitis

Abstract: Pharmacological treatment with rGal-1 reduces clinical signs of atopic dermatitis. Systemic treatment with rGal-1 inhibits eosinophil and mast cell influx in the skin of AD animals. rGal-1 reduced local eotaxin levels and systemic IL-17 levels. The inhibition of disease progression induced by rGal-1 was correlated with upregulation of phosphorylated ERK.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 36 publications
6
22
0
Order By: Relevance
“…Galectin-1 is a β-galactoside-binding mammalian lectin which has anti-inflammatory features. 44 Galectin-1 attenuates the inflammatory response by reducing neutrophil migration to sites of acute inflammation, 20,45 inhibiting production of nitric oxide by macrophages, 46 preventing adhesion of T cells to extracellular matrix and down-regulating their production of TNF-α 47 and also inducing IL-10…”
Section: Biochemical Resultsmentioning
confidence: 99%
“…Galectin-1 is a β-galactoside-binding mammalian lectin which has anti-inflammatory features. 44 Galectin-1 attenuates the inflammatory response by reducing neutrophil migration to sites of acute inflammation, 20,45 inhibiting production of nitric oxide by macrophages, 46 preventing adhesion of T cells to extracellular matrix and down-regulating their production of TNF-α 47 and also inducing IL-10…”
Section: Biochemical Resultsmentioning
confidence: 99%
“…WT and AnxA1 -/- mice were distributed in three experimental groups: Naïve, Sham and AD. On days 0 and 7, animals were immunized with a subcutaneous injection of 5 µg of ovalbumin (OVA, grade C; Sigma-Aldrich, St Louis, MO, USA) and 10 mg/mL of aluminum hydroxide adjuvant diluted in 200 µL of sterile saline according to previous studies [18]. On day 11, animals were shaved and the hair removed from the entire back.…”
Section: Methodsmentioning
confidence: 99%
“…In view of the multifaceted immunoregulatory properties of Gal 1, Correa et al (38) evaluated the possible therapeutic efficacy of intraperitoneally applied recombinant Gal 1 on an ovalbumininduced atopic dermatitis model in BALB/c mice. In Gal 1-treated mice they found that Gal 1 was as effective as dexamethasone in causing clinically evident improvement of skin lesions, reduction in local eotaxin and interferon-gamma levels, suppression of eosinophil and mast cell infiltration, decrease of interleukin 17 plasma levels, activation of signal-regulated kinase, and downregulation of endogenous Gal 1.…”
Section: B Atopic Dermatitismentioning
confidence: 99%